Effects of nitrogen fertilization and planting density on intermediate wheatgrass yield. (17th August 2020) - Fernandez, Christopher W.; Ehlke, Nancy; Sheaffer, Craig C.; Jungers, Jacob M.
Abstract: Perennial crops have the potential to provide food, feed, fuel, and fiber while promoting multiple ecosystem services. Intermediate wheatgrass (IWG) [ Thinopyrum intermedium (Host) Buckworth & Dewey] is a perennial grass being bred for grain production. Because the development of IWG as a grain crop is still in its infancy, basic agronomic management practices needed to maximize grain yield and profitability remain unclear. We conducted an experiment to test the effect of N fertilizer rate and type (synthetic vs. organic) and planting density on grain and forage yield of IWG at two sites in Minnesota over 3 yr. Nitrogen application had no effect on grain yield in Year 1 but increased yields in Years 2 and 3. Reducing planting density from 145 to 36 seeds m −2 reduced grain yield in Year 1 but increased grain yield in subsequent years, particularly when coupled with inorganic N fertilizer applied at 80 kg N ha −1 . A high proportion of fertile tillers was the best predictor of high IWG grain yield, suggesting that shifts toward vegetative growth over sexual reproduction in the years following establishment are associated with grain yield declines. Generally, biomass yield responded positively to increasing N application rates and planting density across all years. Our results indicate that optimizing plant breeding and agronomic practices that promote fertile tiller production will be critical to the future management of IWG as a perennial grain crop.